Skeletal muscle ischemia and reperfusion in rats increase lipid peroxidation in rats - Piccinato,Carlos Eli (2004)
PURPOSE: To determine the effects of 30 minutes of ischemia followed by 30 minutes of reperfusion in skeletal muscle of rats receiving three different diets (supplemented, normal and vitamin E deficient) on lipoperoxidation (LP). METHODS: LP measured by TBARS levels, and plasma and hepatic concentrations of vitamin E measured by HPLC. RESULTS: The deficient group presented higher lipoperoxidation levels in muscle compared to the control and supplemented groups. CONCLUSION: Supplementation with vitamin E decrease the free radicals production in ischemia/reperfusion in skeletal muscle of rats.